Composite diaphragm and battery using same
By introducing modified lithium titanate materials into the separator of lithium-ion batteries, the problem of poor thermal stability of existing separators at high temperatures is solved, and the battery energy density is improved and the risk of thermal runaway is reduced.
Patent Information
- Application Number
- CN202411817878.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The polyolefin separators of existing lithium-ion batteries have poor thermal stability at high temperatures, which can easily lead to degradation in battery performance and risk of thermal runaway.
A composite separator design is adopted, which includes a substrate layer and an active layer, in which a modified lithium titanate material is used, which is coated with fluorine element doping and carbon material to form semi-ionic C-F bonds to enhance electrical conductivity and thermal stability.
It improves the energy density of the battery and the thermal stability of the diaphragm, reduces the risk of thermal runaway, and extends the cycle life of the battery.
Smart Images

Figure BDA0005182464330000031 
Figure BDA0005182464330000091 
Figure BDA0005182464330000092
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a composite diaphragm and a battery using the same. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely used in various fields such as portable electronics, electric vehicles and grid energy storage due to their high energy density, long cycle life and environmental friendliness. Compared with other non-polyolefin separators, polyolefin separators such as polyethylene (PE) and polypropylene (PP) are often used in lithium-ion batteries due to their low cost and balanced performance; however, they also have some disadvantages, such as poor wettability, low thermal stability and susceptibility to lithium dendrite growth, which can lead to poor battery performance, capacity decay, and even thermal runaway and explosion under certain conditions.
[0003] In the prior art, in order to solve the above problems, a multi-layer composite diaphragm structure is usually used, such as PP and PE composite design to prepare the diaphragm. In this design, the layer with a lower melting point will melt at high temperature and close the pores, thereby stopping ion transmission and reducing the risk of thermal runaway. However, this multi-layer structure will increase the thickness of the diaphragm and reduce the energy density of the battery. At the same time, intermittent local temperature changes will lead to a reduction in the ion conduction area and even cause the battery to fail. Summary of the invention
[0004] In order to ensure that the battery has good energy density and improve the stability of the diaphragm, the present invention provides a composite diaphragm and a battery using the same.
[0005] According to one aspect of the present application, a composite diaphragm is provided, which includes a substrate layer and an active layer located on at least one side of the surface of the substrate layer, and the active layer includes a modified lithium titanate material; wherein the modified lithium titanate material includes an inner core layer and an outer shell layer, the inner core layer includes fluorine-doped lithium titanate, and the outer shell layer includes a carbon material.
[0006] The present invention can not only improve the energy density of the battery by introducing a modified lithium titanate material into the diaphragm, but also improve the stability of the diaphragm by preventing the thermal shrinkage of the diaphragm and enhancing the thermal stability of the diaphragm. Specifically, firstly, fluorine doping in the lithium titanate material can accelerate the transfer of electrons from the surface to the electrolyte, and fluorine doping can form oxygen and titanium vacancies in the lithium titanate material, thereby increasing the internal electron concentration of the lithium titanate material and enhancing its electronic conductivity and electronic conductivity. Secondly, the fluorine element in the inner core layer of the modified lithium titanate material and the carbon material in the outer shell layer can form a semi-ionic CF bond, thereby increasing the defects of the carbon layer, generating more adsorption active sites, and forming a synergistic enhancement of the conductive effect of the modified lithium titanate material. Therefore, the introduction of modified lithium titanate materials can improve the energy density of the battery. On the other hand, through the outer shell layer, the thermal shrinkage problem of the diaphragm can be improved, thereby improving the thermal stability of the diaphragm.
[0007] Preferably, the substrate layer includes at least one of polyethylene (PE) and polypropylene (PP).
[0008] Preferably, in the fluorine-doped lithium titanate, the mass content of the fluorine element is 1-2%.
[0009] Preferably, the carbon material is a nitrogen-doped carbon material. Further, nitrogen doping in the carbon material helps to increase the defects of the carbon material, thereby changing the electronic conductivity of the material and providing additional adsorption sites for Li and Ti in the modified lithium titanate material, thereby improving the capacity and rate performance of the modified lithium titanate material composite material.
[0010] Preferably, in the nitrogen-doped carbon material, the mass content of nitrogen element is 1-5%.
[0011] Preferably, the particle size of the modified lithium titanate material is 500-600 nm.
[0012] Preferably, the thickness of the outer shell layer is 50-100 nm.
[0013] Preferably, the preparation of modified lithium titanate material includes the following steps: S1. Mixing a carbon source, a titanium source, a lithium source, and a nitrogen source, and reacting the mixture at 600-800°C for 6-8 hours in an inert gas atmosphere to obtain a nitrogen-doped carbon-coated titanium material; S2. Mixing the nitrogen-doped carbon-coated titanium material with a fluorine source, and reacting the mixture at 200-400°C for 2-3 hours in an inert gas atmosphere to obtain a modified lithium titanate material.
[0014] Preferably, the carbon source comprises trimethylolpropane (C6H 14 O3).
[0015] Preferably, the titanium source comprises metatitanic acid (H2TiO3).
[0016] Preferably, the nitrogen source comprises dopamine hydrochloride.
[0017] Preferably, the fluorine source comprises ammonium fluoride particles (NH4F).
[0018] Preferably, calculated by mass ratio, carbon source: titanium source: nitrogen source = 0.5-1:1.5-2:1-2.
[0019] Preferably, the active layer further includes a conductive agent, and the conductive agent includes at least one of Ketjen black (KB), conductive carbon black (SP), and carbon nanotubes (CNTS).
[0020] Preferably, the active layer further includes a binder, and the binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTF), and polyacrylic acid (PAA).
[0021] Preferably, in the active layer, calculated by mass ratio, the modified lithium titanate material: the conductive agent: the binder = 80-90: 5-10: 5-10.
[0022] Preferably, the composite diaphragm comprises a substrate layer, a reinforcement layer, and an active layer arranged in sequence; wherein the reinforcement layer comprises an inorganic nanomaterial, and the inorganic nanomaterial comprises at least one of alumina ceramic nanoparticles, titanium dioxide, and silicon dioxide. Furthermore, by introducing the reinforcement layer, the wettability and thermal stability of the composite diaphragm electrolyte can be improved.
[0023] Preferably, the particle size of the inorganic nanomaterial is 1 to 100 nm.
[0024] Preferably, the thickness of the composite membrane is 30-40 μm, and the thickness of the active layer is 15-25 μm.
[0025] Preferably, the thickness of the reinforcement layer is 1-2 μm.
[0026] A second aspect of the present invention provides a battery, comprising the composite separator as described above. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0028] Example 1
[0029] 1. Materials required for composite diaphragm
[0030] The materials required for preparing the composite membrane in this embodiment are shown in Table 1.
[0031] Table 1. Materials for preparing composite membranes
[0032]
[0033] 2. Preparation of modified lithium titanate materials
[0034] In this embodiment, the modified lithium titanate material is prepared according to the following method.
[0035] S1. 1g trimethylolpropane (C6H 14 O3) particles were dissolved in 800 mL of deionized water, stirred for 25 minutes to prepare a buffer solution, then 2 g of H2TiO3 powder was added and stirred for 30 minutes, and then 1.5 g of dopamine hydrochloride was added and stirred for 4.5 hours, centrifuged and dried to obtain a precursor; then the precursor was ground and mixed with lithium carbonate, and the mixture was heated to about 750°C in a nitrogen environment at a heating rate of 5°C per minute for 7 hours to obtain a nitrogen-doped carbon-coated titanium material;
[0036] S2. The nitrogen-doped carbon-coated titanium material and ammonium fluoride (NH4F) are mixed and ground, and then the mixture is heated to 300°C in a nitrogen environment and kept warm for 2.5 hours to obtain a modified lithium titanate material.
[0037] Among them, in the modified lithium titanate material prepared in this embodiment, the mass content of nitrogen element is 3%, the mass content of fluorine element is 1.5%, and the particle size is 560nm.
[0038] 3. Preparation of Composite Diaphragm
[0039] In this embodiment, the composite membrane is prepared according to the following method.
[0040] Firstly, a first slurry is prepared by mixing alumina ceramic nanoparticles with PVDF, and the mass ratio is calculated as alumina ceramic nanoparticles: PVDF = 0.9:0.1. The first slurry is coated on the surface of the substrate layer to form a reinforcement layer. Subsequently, the prepared modified lithium titanate material is mixed with KB and PVDF in a weight ratio of 90:5:5 in N-methylpyrrolidone (NMP) solvent to obtain a second slurry. The second slurry is coated on the surface of the reinforcement layer, and the slurry is dried at 60°C to finally obtain a composite diaphragm.
[0041] 4. Preparation of Cells
[0042] The positive electrode slurry is prepared by stirring LFP:SP:PVDF in a mass ratio of 97.4:0.9:1.7, and the negative electrode slurry is prepared by stirring graphite:SP:CMC:SBR in a mass ratio of 96.7:0.6:1.2:1.5. The prepared positive and negative electrode slurries are respectively coated on both sides of the current collector, passed through an oven, roller pressed, and then rolled up; the positive and negative electrodes are cut into pole pieces of a certain size, and stacked into a core package by a negative electrode-modified separator-positive electrode stacking method, and finally the core package is put into a shell to be assembled into a battery.
[0043] Example 2
[0044] This example prepares modified lithium titanate materials, composite diaphragms and batteries using the same with reference to the formula and method provided in Example 1. The difference from Example 1 is that the mass content of fluorine in the modified lithium titanate material prepared in this example is 2% (achieved by adjusting the content of NH4F added). Except for the above difference, the operating steps for preparing modified lithium titanate materials, composite diaphragms and batteries using the same in this example are strictly consistent with those in Example 1.
[0045] Example 3
[0046] This embodiment refers to the formula and method provided in Example 1 to prepare a modified lithium titanate material, a composite diaphragm, and a battery using the same. The difference from Example 1 is that this embodiment does not dope the modified lithium titanate material with nitrogen. In addition to the above differences, the operation steps for preparing the modified lithium titanate material, the composite diaphragm, and the battery using the same in this embodiment are strictly consistent with those in Example 1. Specifically, the method for preparing the modified lithium titanate material in this embodiment is:
[0047] S1. 1g trimethylolpropane (C6H 14 O3) particles were dissolved in 800 mL of deionized water, stirred for 25 minutes to prepare a buffer solution, then 2 g of H2TiO3 powder was added and stirred for 30 minutes, centrifuged and dried to obtain a precursor; then the precursor was ground and mixed with lithium carbonate, and the mixture was heated to about 750°C at a heating rate of 5°C per minute in a nitrogen environment for 7 hours to obtain a carbon-coated titanium material;
[0048] S2. The carbon-coated titanium material and ammonium fluoride particles (NH4F) are mixed and ground, and then the mixture is heated to 300°C in a nitrogen environment and kept warm for 2.5 hours to obtain a modified lithium titanate material.
[0049] Example 4
[0050] This example prepares modified lithium titanate materials, composite diaphragms, and batteries using the same with reference to the formula and method provided in Example 1. The difference from Example 1 is that the modified lithium titanate material prepared in this example has a nitrogen content of 5% by mass (achieved by regulating the content of dopamine hydrochloride added). Except for the above differences, the operating steps for preparing modified lithium titanate materials, composite diaphragms, and batteries using the same in this example are strictly consistent with those in Example 1.
[0051] Example 5
[0052] This example prepares modified lithium titanate materials, composite diaphragms, and batteries using the same with reference to the formula and method provided in Example 1. The difference from Example 1 is that the particle size of the modified lithium titanate material prepared in this example is 500 nm, and the thickness of its carbon coating layer is 100 nm (achieved by regulating the reaction temperature and time for preparing the modified lithium titanate material). Except for the above differences, the operating steps for preparing the modified lithium titanate materials, composite diaphragms, and batteries using the same in this example are strictly consistent with those in Example 1.
[0053] Example 6
[0054] This example prepares modified lithium titanate materials, composite diaphragms, and batteries using the same with reference to the formula and method provided in Example 1. The difference from Example 1 is that the particle size of the modified lithium titanate material prepared in this example is 600 nm, and the thickness of its carbon coating layer is 50 nm (achieved by regulating the reaction temperature and time for preparing the modified lithium titanate material). Except for the above differences, the operating steps for preparing the modified lithium titanate materials, composite diaphragms, and batteries using the same in this example are strictly consistent with those in Example 1.
[0055] Example 7
[0056] This example prepares modified lithium titanate materials, composite diaphragms and batteries using the same with reference to the formula and method provided in Example 1. The difference from Example 1 is that this example does not provide a reinforcement layer when preparing the composite diaphragm. Apart from the above differences, the operating procedures for preparing modified lithium titanate materials, composite diaphragms and batteries using the same are strictly consistent with those in Example 1.
[0057] Comparative Example 1
[0058] This comparative example prepares a battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the battery, this comparative example uses an ordinary PE diaphragm instead of a composite diaphragm. Except for the above difference, the operation steps for preparing the battery in this example are strictly consistent with those in Example 1. In this comparative example, the thickness of the diaphragm is 12 μm.
[0059] Comparative Example 2
[0060] This comparative example uses the formula and method provided in Example 1 to prepare a composite diaphragm and a battery. The difference from Example 1 is that no active layer is introduced when preparing the composite diaphragm. Except for the above difference, the operation steps for preparing the battery in this comparative example are strictly consistent with those in Example 1. In this comparative example, the thickness of the composite diaphragm is 13 μm.
[0061] Comparative Example 3
[0062] This comparative example refers to the formula and method provided in Example 1 to prepare a composite diaphragm and a battery. The difference from Example 1 is that when preparing the composite diaphragm, this comparative example does not introduce a reinforcement layer, and replaces the modified lithium titanate material with an equal mass fraction of lithium titanate in the active layer. Except for the above differences, the operation steps for preparing the battery in this comparative example are strictly consistent with those in Example 1. In this comparative example, the thickness of the composite diaphragm is 32μm.
[0063] Specifically, the method for preparing lithium titanate in this comparative example is:
[0064] 1.0 g of H2TiO3 powder was mixed with 2.0 g of Li2CO3 and ground in an agate mortar for 1 hour. The mixture was then heated to about 750°C at a heating rate of 5°C per minute in a nitrogen atmosphere for 7 hours.
[0065] Comparative Example 4
[0066] This comparative example refers to the formula and method provided in comparative example 3 to prepare a composite diaphragm and a battery. The difference from comparative example 3 is that when preparing the composite diaphragm, this comparative example introduces a reinforcement layer between the substrate layer and the active layer, wherein the material and thickness of the reinforcement layer refer to the formula provided in Example 1. Except for the above difference, the operation steps for preparing the battery in this comparative example are strictly consistent with those in comparative example 3. In this comparative example, the thickness of the composite diaphragm is 33 μm.
[0067] Test Case
[0068] 1. Test subjects
[0069] Composite diaphragms and batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 4.
[0070] 2. Test Method
[0071] (1) Tensile strength: Use a tensile testing machine, set a constant tensile speed, record the breaking load, and calculate the tensile strength.
[0072] (2) Thermal shrinkage: The sample is heated to cause it to shrink during the heating process, and then the dimensional change before and after shrinkage is measured to calculate the shrinkage rate.
[0073] (3) Electrolyte absorption rate: Add equal amounts of electrolyte to the center of the prepared measuring diaphragms, and measure the amount of electrolyte absorbed by each measuring diaphragm within a certain period of time.
[0074] (4) Ionic conductivity: The conductivity is tested using the four-probe method, which uses four equally spaced metal probes to contact the sample surface. By measuring the voltage and current between the probes, the resistance value of the sample is obtained, and finally the conductivity is calculated.
[0075] (5) Capacity density: At an ambient temperature of 25±2℃, discharge the battery at a constant current of 0.33C to 2.5V and leave it for 10min. Then charge the battery at a constant current of 0.33C to 3.65V, and then switch to constant voltage charging at 3.65V until the charging current is less than or equal to 0.05C. Leave it for 30min. The battery is discharged at different rates of constant current until the voltage reaches 2.5V, and then left for 30min. The discharge capacity C is recorded. X , the prepared battery weight is m, energy density = C X / m.
[0076] 3. Test results and analysis
[0077] The test results of this test case are shown in Table 2 and Table 3.
[0078] The battery diaphragm must have good thermal stability, because high temperature can cause internal short circuit, thermal runaway and explosion, thus affecting the safety performance of the battery. In this test example, the diaphragms of Example 1 and Comparative Examples 1 to 4 were exposed to different temperatures of 120 to 160°C for 30 minutes, and the mechanical properties and thermal shrinkage of the diaphragms were measured. Specifically, the bare PE diaphragm shrank by 16% at 120°C, while the composite diaphragms of Comparative Examples 2, 3, 4 and Example 1 did not shrink at all. Furthermore, the diaphragms of Comparative Examples 2 and 3 began to shrink at 140°C, with shrinkage rates of 13% and 10%, respectively; the diaphragms of Comparative Example 4 and Example 1 did not begin to shrink until 160°C, with shrinkage rates of only 1.5% and 1.4%. The shrinkage rates of other diaphragms at 160°C were much higher: 55% for bare PE, 23% for the diaphragm provided in Comparative Example 2, and 17% for the diaphragm provided in Comparative Example 3. This shows that the composite diaphragm provided by the present invention can greatly improve the thermal stability of the diaphragm.
[0079] In addition, in this test, the mechanical properties of the separators provided in Example 1 and Comparative Examples 1 to 4 were also tested. Among them, the separators provided in Example 1, Comparative Example 3 and Comparative Example 4 have high tensile strength, which can prevent the problem of internal short circuit between electrodes when pressure changes occur during operation of the battery.
[0080] Furthermore, the present invention also tests the electrolyte absorption rate of the diaphragms provided in Example 1 and Comparative Examples 1 to 4 and the electrochemical performance of the batteries using the same. Among them, it can be confirmed by the data that the composite diaphragm prepared in Example 1 has the highest electrolyte absorption rate, reaching 124%, which proves its high affinity with the liquid electrolyte. In addition, the battery using the composite diaphragm prepared in Example 1 also has better ion conductivity and capacity density. This may be because the modified lithium titanate material provided by the present invention, the nitrogen-doped carbon material in its outer shell layer can limit the total particle size of the modified lithium titanate to the range of 500 to 600 nm, and the nanostructure shortens the ion diffusion path. In addition, the carbon layer doped with nitrogen elements can form oxygen and titanium vacancies in the lithium titanate material, increase the electronic conductivity of the material, and the carbon layer defects provide additional adsorption active sites for lithium ions. As for the inner core layer of the modified lithium titanate material, firstly, fluorine doping increases the concentration of oxygen vacancies in lithium titanate and improves the conductivity of lithium titanate; secondly, fluorine doping increases the asymmetry of the carbon network by forming semi-ionic CF bonds with carbon materials, forming semi-ionic CF bonds, thereby increasing the defects of the carbon layer and generating more adsorption active sites.
[0081] Therefore, compared with the separators provided in Comparative Examples 1 and 2, the active layer in the composite separator provided in Example 1 can not only participate in the electrochemical reaction and provide additional capacity, but also has little effect on the diffusion of lithium ions, and can achieve fast and stable battery performance at high rates; in addition, the active layer can also improve the stability of the separator by preventing thermal shrinkage and enhancing thermal stability. Therefore, compared with the existing separators, the composite separator provided by the present invention has higher capacity, higher coulombic efficiency and longer cycle life.
[0082] Table 2. Test results of capacity density at different rates in this test example
[0083]
[0084] Furthermore, by comparing the data of Examples 1 to 4, it can be seen that the nitrogen content and fluorine content in the modified lithium titanate material will also affect the performance of the composite diaphragm, specifically, the electronic conductivity of the battery using it. And from the data of Examples 5 and 6, it can be seen that the particle size of the modified lithium titanate material and the thickness of the gas shell layer will also affect the performance of the composite diaphragm.
[0085] In addition, by comparing the data of Example 1, Example 7 and Comparative Example 3, it can be seen that the wettability and thermal stability of the composite diaphragm electrolyte can be improved by introducing the reinforcement layer.
[0086] Table 3. Test results of this test case
[0087]
[0088] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a substrate layer and an active layer located on at least one side of the surface of the substrate layer, wherein the active layer comprises a modified lithium titanate material; The modified lithium titanate material comprises a core layer and an outer shell layer, the core layer comprises fluorine-doped lithium titanate, and the outer shell layer comprises a carbon material.
2. The composite diaphragm according to claim 1, characterized in that: In the fluorine-doped lithium titanate, the mass content of fluorine is 1-2%.
3. The composite diaphragm according to claim 1, characterized in that: The carbon material is a nitrogen-doped carbon material.
4. The composite diaphragm according to claim 3, characterized in that: In the nitrogen-doped carbon material, the mass content of nitrogen element is 1-5%.
5. The composite diaphragm according to claim 1, characterized in that: The particle size of the modified lithium titanate material is 500-600 nm.
6. The composite diaphragm according to claim 1, characterized in that: The thickness of the outer shell layer is 50-100 nm.
7. The composite diaphragm according to claim 1, characterized in that: The preparation of the modified lithium titanate material comprises the following steps: S1. A carbon source, a titanium source, a lithium source and a nitrogen source are mixed, and the mixture is reacted at 600 to 800 ° C for 6 to 8 hours in an inert gas atmosphere to obtain a nitrogen-doped carbon-coated titanium material; S2. The nitrogen-doped carbon-coated titanium material is mixed with a fluorine source, and the mixture is reacted at 200 to 400° C. for 2 to 3 hours in an inert gas atmosphere to obtain the modified lithium titanate material.
8. The composite diaphragm according to claim 1, characterized in that: The composite diaphragm comprises the substrate layer, the reinforcement layer, and the active layer arranged in sequence; Wherein, the reinforcement layer comprises inorganic nanomaterials, and the inorganic nanomaterials comprise at least one of alumina ceramic nanoparticles, titanium dioxide, and silicon dioxide.
9. The composite diaphragm according to any one of claims 1 to 8, characterized in that: The thickness of the composite membrane is 30-40 μm, and the thickness of the active layer is 15-25 μm.
10. A battery, characterized in that: The battery comprises the composite separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
A separating membrane used for a lithium ion battery, a preparing method thereof and the lithium ion battery
CN106558664A
High specific energy lithium titanate material, battery and preparation method of battery
CN109860583A
High energy density lithium ion secondary battery
CN109860584A
Functionalized polyolefin composite diaphragm and preparation method and application thereof
CN111725466A
Lithium ion battery diaphragm coated with negative electrode active material and preparation method and application of lithium ion battery diaphragm
CN113839146A